Lack of transplacental transmission of Bartonella bovis. (February 2015) - Chastant-Maillard, S.; Boulouis, H.-J.; Reynaud, K.; Thoumire, S.; Gandoin, C.; Bouillin, C.; Cordonnier, N.; Maillard, R.
Highlights: To assess the vertical transmission of Bartonella in cattle. Fifty-six cow-calf pairs were tested for Bartonella bacteremia and/or serology. None of the 29 (52%) bacteremic cows gave birth to bacteremic calves. B. bovis was not detected in placental cotyledons. Transplacental transmission of B. bovis and multiplication of the bacteria in the placenta do not seem likely. Abstract: Transplacental transmission of Bartonella spp. has been reported for rodents, but not for cats and has never been investigated in cattle. The objective of this study was to assess vertical transmission of Bartonella in cattle. Fifty-six cow-calf pairs were tested before (cows) and after (calves) caesarean section for Bartonella bacteremia and/or serology, and the cotyledons were checked for gross lesions and presence of the bacteria. None of the 29 (52%) bacteremic cows gave birth to bacteremic calves, and all calves were seronegative at birth. Neither placentitis nor vasculitis were observed in all collected cotyledons. Bartonella bovis was not detected in placental cotyledons. Therefore, transplacental transmission of B. bovis and multiplication of the bacteria in the placenta do not seem likely. The lack of transplacental transmission may be associated with the particular structure of the placenta in ruminants or to a poor affinity/agressiveness of B. bovis for this tissue.